Analisis Faktor Kepatuhan Minum Obat Pasien Skizofrenia di Poli Mentari Puskesmas Kecamatan Kalideres (Analisis Data Sikda Tahun 2019) - Desi Susanti; Pradnya Paramita; Abdullah Antaria (Universitas Muhammadiyah Semarang, 2022)
Background: Schizophrenia is a mental disorder that causes a person to become physiologically dysfunctional for himself and for social interactions. Compliance with taking medication is very important for schizophrenic patients so that patients can recover and prevent relapse. Methods: Adherence to taking medication includes the correct behavior of an individual with medical advice, the use of drugs according to the instructions and includes the use at the right time. This research uses quantitative analytic research with cross sectional method complemented by qualitative research. Results: The results showed 201 schizophrenic patients who met the inclusion criteria as many as 198 patients. The results of univariate, bivariate and multivariate analysis showed that patients aged 0-30 years were 59.1%. Factors related to medication adherence are distance to health care facilities and disease history. And the most dominant factor from the multivariate results was a history of disease with an OR of 17.815. Conclusion: To improve medication adherence for schizophrenic patients, various supports are needed both within themselves (the patient) and outside of the patient's factors so that they can assist in the treatment process and the patient's recovery.